Digging The ‘Dirt’: Roots and Routes of Stigma - Sharif, Aditi; Ferdousy Mithila, Mahima (South Asian Journal of Social Sciences and Humanities, 2024)
Historically, Dalit identity is associated with different stereotypical notions. In this article, we have attempted to explore the underlying factors behind the stigma associated with them from the micro perspective in a small Muslim-dominated context of Bangladesh based on a series of intensive fieldwork. It reveals that Dalit cleaners are widely considered impure, dirty, strange, chaotic, alcoholic, and inferior. We combined two theoretical perspectives to interpret the matter systematically: Douglas’s notion of purity and pollution and Foucauldian discourse.  The apparent reasons for the stigma associated with Dalit cleaners at Bhairab are association with ‘Dirty jobs, pig rearing, pork consumption, liquor consumption, and business. However, the empirical pieces of evidence show that different historical, religious, and socio-political factors (such as ideological domination of Hindu scriptures, the intervention of British colonialism, and the negative role of media and local influential businessmen) contribute significantly to the stigma.
Keywords: Dalit; Discourse; Stigma; Purity; Pollution